2023
DOI: 10.3390/vaccines11050912
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Parental Consent to Human Papillomavirus Vaccine Uptake by Their Adolescent Daughters in ZAMBIA: Application of the Health Belief Model

Abstract: Parental consent for adolescent human papillomavirus (HPV) vaccine uptake is important; however, refusal is prevalent. Therefore, this study aimed to understand factors associated with parental consent for their adolescent daughter’s HPV vaccination. A cross-sectional study was conducted in Lusaka, Zambia, between September and October 2021. We recruited parents from different social settings. The means and standard deviations or median and interquartile ranges were used as appropriate to summarise continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The study was conducted within health facilities and schools that are located within the six sub-districts of Lusaka. Further details about the study setting and how the HPV vaccination program is implemented in Zambia are reported elsewhere [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study was conducted within health facilities and schools that are located within the six sub-districts of Lusaka. Further details about the study setting and how the HPV vaccination program is implemented in Zambia are reported elsewhere [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, cervical cancer is one of the few preventable cancers, due to HPV vaccination, screening, and early treatment. However, in Zambia, HPV vaccine and cervical cancer screening coverage are low [ 11 , 12 ], just like in many SSA countries [ 2 ], leading to the late presentation of cervical cancer worsened by late diagnosis and delayed treatment at the only national chemoradiation centre [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations